ln(x)-on(4)=0

Simple and best practice solution for ln(x)-on(4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x)-on(4)=0 equation:


Simplifying
ln(x) + -1on(4) = 0

Multiply ln * x
lnx + -1on(4) = 0

Reorder the terms for easier multiplication:
lnx + -1 * 4no = 0

Multiply -1 * 4
lnx + -4no = 0

Solving
lnx + -4no = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '4no' to each side of the equation.
lnx + -4no + 4no = 0 + 4no

Combine like terms: -4no + 4no = 0
lnx + 0 = 0 + 4no
lnx = 0 + 4no
Remove the zero:
lnx = 4no

Divide each side by 'nx'.
l = 4ox-1

Simplifying
l = 4ox-1

See similar equations:

| -25=5(3g+4) | | (9x+10)+(13-9x)= | | 3x^2-2y^2=1 | | z-38=-28 | | 12(5x+9)-11x= | | 25x+7(1.50)=10 | | X^5x=6 | | 5-5x-x=53 | | -1+5x-7x=3 | | 8.4254+.6018R=R | | 6(x+2)=5(x+4) | | 9x^4-19x^2-2=0 | | -3+x=6n+22 | | -30x+12(x-1)=24x+200 | | 5x-y=30(3) | | 5a-5ab= | | 2x=x+14x | | A^2+11a=-30 | | 3+0.4n= | | -11+51=-4(x+5) | | -30x+12(x-1)=24x+2 | | 875/x/60=26.25 | | 7x=1/2*105 | | 5x-4=11+2n | | 9(3x-5)+9x= | | 3(x-4)=23-4c | | 3lnc=2lny | | 6+6x-2x=-10 | | 25t^2+45t=0 | | 5log(5x-10)=15 | | 3ln(2X)=27 | | 10(3x+12)+13x-14= |

Equations solver categories